Developing a brain-based computing system - Aditya Narayanamoorthy (2012)
Artificial intelligence-related methods have long been used to solve problems in real life. These methods include cognitive learning models, where the agent solving the task does so by learning while doing the task and adapting its behaviour accordingly. A related field is brain-based computing, where a neural model is created to better monitor the working of various regions in the brain, which could help us understand how humans complete these tasks.